PENGARUH MODEL BLENDED LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP DAN DISPOSISI MATEMATIS - Rizki Nugraha; Syamsuri Syamsuri (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
Beberapa penelitian sebelumnya mengungkapkan bahwa model blended learning berpengaruh terhadap kemampuan kognitif siswa, namun belum ditemukan mengkaji pengaruhnya terhadap sikap afektif siswa. Tujuan penelitian ini adalah untuk mendeskripsikan pengaruh penerapan model blended learning terhadap pemahaman konseptual dan disposisi matematis siswa. Jenis penelitian ini adalah quasi eksperimen dengan menggunakan rancangan randomized posttest only control group. Populasi dalam penelitian ini ialah seluruh siswa kelas VII MTs Syekh Manshur Pandeglang, Banten pada semester genap tahun ajaran 2021/2022. Sampel yang dipilih adalah dua kelas dengan cluster random sampling. Model blended learning yang digunakan adalah flipped classroom dengan Edmodo sebagai learning management system. Pemahaman konseptual matematis diukur dengan tes dan disposisi matematis diukur dengan kuesioner yang telah valid dan reliabel. Data dianalisis menggunakan MANOVA dengan taraf signifikansi 5% (α=0,05) setelah melalui uji prasyarat. Hasil pengujian hipotesis menunjukkan bahwa model blended learning berpengaruh positif terhadap kemampuan memahami konsep dan disposisi matematis siswa.Numerous antecedent investigations have elucidated the influence of the blended learning model upon students' cognitive capabilities; however, there exists a conspicuous dearth of inquiries concerning its ramifications upon students' affective dispositions. The primary objective of this present study was to expound upon the impact of the application of the blended learning model on the enhancement of mathematical conceptual comprehension and the cultivation of favorable mathematical dispositions among students. This study adopts a quasi-experimental research design, employing a randomized posttest only control group configuration.  The study's target population encompasses all 7th-grade students attending MTs Syekh Manshur Pandeglang, Banten, during the even semesters of the 2021/2022 academic year. Utilizing cluster random sampling, two classes were selected as the sample groups. The employed pedagogical approach within the study is the flipped classroom model, supplemented by the utilization of Edmodo as the designated learning management system. Mathematical conceptual understanding is gauged through comprehensive tests, while mathematical dispositions are assessed using a validated and reliable questionnaire. The dataset comprises both test and non-test data, which were subsequently subjected to thorough scrutiny through a multivariate analysis of variance (MANOVA) at a predefined significance level of 5% (α=0.05), following compliance with the requisite assumptions. The results obtained through hypothesis testing unequivocally demonstrate a salient and affirmative impact of the blended learning model on the enhancement of students' conceptual understanding and the cultivation of positive mathematical dispositions among them.